Comparative study of corrosion behaviors of die cast LA42 and AZ91 alloys - Wenke Zhou; Zixin Li; Dejiang Li; Yuyang Chen; Yao Yang; Ming Qin; Xiaoqin Zeng (Journal of Magnesium and Alloys)
In our previous work, die cast LA42 (Mg–4La–2.5Al–0.3Mn, wt.%) alloy with an excellent combination of thermal-conducting performance and mechanical properties was developed. This study, taking commercial die cast AZ91 (Mg-9Al-1 Zn, wt.%) alloy as a comparison, investigates the microstructure and corrosion behavior of the LA42 alloy in chloride-containing environment. The findings revealed that the microstructure of die cast LA42 alloy displays an Al-depleted α-Mg dendrite and a network shape eutectic phase comprising of eutectic α-Mg and lamellar Al11La3. The LA42 alloy exhibited slightly inferior corrosion resistance and deeper corrosion pits than the AZ91 alloy, which were related to the interphase attack and the presence of a layer of corrosion products containing more magnesium hydroxide of the LA42 alloy. The corrosion behavior of the LA42 alloy was characterized by an interphase attack on the periphery of Al-depleted α-Mg dendrite adjacent to Al11La3, which primarily ascribed to the relatively lower potential of the Al-depleted α-Mg phase and the interfacial reactivity between it and the adjacent Al11La3, whereas the AZ91 alloy showed a trait of preferential corrosion of the interior of α-Mg dendrite for its lowest potential among different phases. This comprehensive research can provide a guidance for future alloy design of Mg-Al-La alloys and their industrial applications.